2015
DOI: 10.1097/mot.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

Role of B cells in tolerance induction

Abstract: Purpose B cells are known to play a central role in humoral immunity and to boost cellular immunity, however, in a variety of experimental models, B cell subsets ameliorate inflammation and autoimmune disease, indicating that they can also play a regulatory role. Here we highlight the advances in regulatory B cell (Breg) biology of the past year with an emphasis on findings pertinent to transplantation. Several recent observations highlight the relevance to clinical transplantation. Data from at least three in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…A frequently described hallmark of Bregs, and the greatest common denominator of all subtypes, is the production of the immunomodulatory cytokine interleukin (IL)‐10 . However, it has become apparent that other mechanisms are at play, and IL‐10 is not always required for B cells to exert immunoregulatory functions . Nevertheless, the phenotypic diversity of Bregs appears to be greater than that of Tregs, and while Tregs are considered a distinct cell lineage, immune regulation may represent a functional state that many types of B cells can acquire in the appropriate context .…”
Section: Introductionmentioning
confidence: 99%
“…A frequently described hallmark of Bregs, and the greatest common denominator of all subtypes, is the production of the immunomodulatory cytokine interleukin (IL)‐10 . However, it has become apparent that other mechanisms are at play, and IL‐10 is not always required for B cells to exert immunoregulatory functions . Nevertheless, the phenotypic diversity of Bregs appears to be greater than that of Tregs, and while Tregs are considered a distinct cell lineage, immune regulation may represent a functional state that many types of B cells can acquire in the appropriate context .…”
Section: Introductionmentioning
confidence: 99%
“…In islet and cardiac allograft models, CD45RB and anti‐CD154 are known to act via Breg cells to enhance graft survival . Thus, an increased potency of Breg function in young recipients than in aged recipients could explain the different effects of B‐cell depletion observed between young and aged transplant recipients.…”
Section: Resultsmentioning
confidence: 99%
“…B cells also act as antigen present cells (APCs) to enhance cellular immunity toward an allograft . In addition to these proimmune functions of B cells, a subpopulation of B cells, termed regulatory B (Breg) cells, has been identified that promote immune regulation by producing IL‐10 . Hence, B‐cells play important and diverse roles that can either enhance or suppress immunity toward organ allografts.…”
Section: Introductionmentioning
confidence: 99%
“…B-lineage lymphoblasts have very low expression of T-cell costimulatory molecules and are poor antigen presenting cells. 25 In addition, recent data suggest that B cells may induce tolerance during lymphopenic states, 26 as may be seen in the posttransplant setting. To overcome this obstacle, DLI was given concurrently with the DC vaccine, which at the low dose of 1 x 10e6 CD3/kg was well tolerated, did not lead to severe GVHD and may have contributed to the immune responses seen in this setting.…”
Section: Discussionmentioning
confidence: 97%